Management of preterm low birth weight infants in Dhaka: a comparison between Standard Care and Kangaroo Mother Care - Mousumi Akter; Salamat Khandker; Mohammad Shaheen; Nadira Mehriban; Sk Akhtar Ahmad (Hygeia Press di Corridori Marinella, 2020)
In Bangladesh, government healthcare facilities are adopting Kangaroo Mother Care (KMC) more extensively for preterm low birth weight (LBW) infants to reduce neonatal deaths in the country. A quasi-experimental study was carried out to compare KMC and Standard Care (SC) outcomes for preterm LBW babies. Data were collected from December 2017 to June 2018. The study focused on the preterm neonates admitted to Bangabandhu Sheikh Mujib Medical University (BSMMU) Hospital, Dhaka. A total of 25 neonates under KMC and 25 neonates under SC were enrolled from the initial study population. The study revealed that during the length of hospital stay, the incidence of hypothermia (4% in KMC vs. 24% in SC) and hyperthermia (8% in KMC vs. 32% in SC) and clinical late-onset sepsis (36% in KMC vs. 64% in SC) were significantly lower among neonates of KMC. Times to first feed (1.80 ± 0.40 in KMC vs. 2.20 ± 0.42 in SC) and to full enteral feeding (8.32 ± 2.49 in KMC vs. 19.56 ± 6.80 in SC) were also found to be significantly shorter among KMC neonates. Moreover, KMC mothers show adequate breastfeeding more often than in SC group (88% in KMC vs. 64% in SC). On the other hand, a higher proportion of SC neonates compared to KMC neonates were found to have feeding intolerance (56% in SC vs. 8% in KMC), hyperglycaemia (24% in SC vs. 4% in KMC) and apnoea (32% in SC vs. 8% in KMC). Finally, mean hospital stay (12.04 ± 2.74 days in KMC vs. 25.24 ± 7.20 days in SC) and mean treatment cost (9,508 ± 4,142 Taka in KMC vs. 35,064 ± 13,352 Taka in SC) were found to be significantly lower for KMC. In conclusion, KMC seems to be a safe and effective method of care for preterm LBW infants in a limited resources health care setting.